Updates in postoperative imaging modalities following musculoskeletal surgery - Thippeswamy, PB; Nedunchelian, M; Rajasekaran, RB; Riley, D; Khatkar, H; Rajasekaran, S (Elsevier, 2021)
Postoperative imaging following orthopaedic surgeries is essential in assessing complications post-surgery and also helps plan further treatment. Combining a high degree of clinical insight with appropriate imaging can guide the treating clinician to the correct diagnosis. Imaging is quite challenging because of surgery-related soft tissue changes, especially in the early postoperative period and the presence of metal implants resulting in image scatter and metal artifacts. Newer modalities and advances in imaging have helped overcome shortcomings and assess better, especially in procedures that involve implants. Collaborative decision-making involving radiologists and clinicians has shown to be beneficial and is the way forward. This narrative review discusses the utility of imaging in evaluating postoperative complications following musculoskeletal surgeries with specific relation to trauma, arthroplasty, and tumour by discussing commonly encountered clinical scenarios.